Catalytic and Process Study of the Selective Hydrogenation of Acetylene and 1,3-Butadiene - Hou, Ruijun; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This thesis offers novel methods for catalyst and process design for the selective hydrogenation of acetylene and 1,3-butadiene. The author predicts the properties of supported Pd-Ni bimetallic catalysts using density functional theory (DFT) calculations and temperature-programmed desorption (TPD). The excellent correlation between model surfaces and supported catalysts demonstrates the feasibility of designing effective bimetallic catalysts for selective hydrogenation reactions. The author also proposes a method for designing non-precious metal catalysts to replace precious metals. She modifies the process of selective hydrogenation of acetylene by coupling the selective adsorption to the selective hydrogenation in the liquid phase, as a result of which the ethylene selectivity is greatly improved and heat transfer is greatly enhanced. Lastly, by analyzing the mechanism of liquid-phase hydrogenation, the author proposes a multi-stage slurry bed reactor for industrial applications.<.
Introduction -- Experimental and Theoretical Methods -- Design of Pd-Ni Bimetallic Catalyst -- Effect of Oxide Supports on Pd-Ni Bimetallic Catalysts -- Replacing Precious Metals with Carbide Catalysts -- Liquid Phase Hydrogenation of Acetylene -- Conclusion.
Keywords: Catalysis; Chemistry, Physical and theoretical; Chemistry, Technical; Chemistry, Organic; Catalysis; Theoretical Chemistry; Industrial Chemistry; Organic Chemistry